Sindicalismo cidadão e economia solidária: uma análise da experiência política da Central Única dos Trabalhadores (CUT) - Corrêa, João Guilherme de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The work that the reader has at hand is a critical analysis about the transformations in the political strategy of the Central Union of Workers (CUT), which led it to promote solidarity economy practices by entities created solely for this. The mode of union action called citizen unionism practiced by the entity and influenced greatly by its most prominent political trend was responsible for consolidating in the 2000s the primacy of political participation in institutional spaces in society and the structure of government and for advancing the practice of provision of social services in parallel to the state and within the design of services and entities nonstate public and the third sector, common in the neoliberal moment.Regarding the provision of services, the Solidarity Development Agency (ADS) was created for acting on employment policy, assisting in the promotion of alternative employment and income for workers outside the formal market, under the predominant form of cooperatives. The policy justification for such actions anchor in the solidarity economy movement in Latin America in general, says seeking activate a type of involvement of civil society marked by another, distinct economic rationality of capitalist. At the level of theoretical elaboration of the proposal adds a residual CUT socialist discourse reconfigured according to the version of Paul Singer, who advocates the necessity for the construction of socialist implants for the realization of a peaceful transition to the new society transformed. Starting this understanding, socialism would be achieved without the need to counteract class interests and without eliminating the capital itself, just that cooperative economic ventures internally to practice democratic management and establish economic relations with justice and solidarity on the basis that from its generalization in society, contaminate capitalist ...

O trabalho que o leitor tem em mãos é uma análise crítica sobre as transformações na estratégia política da Central Única dos trabalhadores (CUT) que a levaram a promover práticas em economia solidária através de entidades criadas exclusivamente para isso. A modalidade de ação sindical chamada sindicalismo cidadão praticada pela entidade e influenciada sobremaneira por sua tendência política mais preeminente foi responsável por consolidar nos anos 2000 a primazia pela participação política em espaços institucionais na sociedade e na estrutura do Estado e por avançar na prática de prestação de serviços sociais paralelamente ao Estado e dentro da concepção dos serviços e entidades “públicos não estatais” e do “terceiro setor”, comuns no momento neoliberal. No que tange a prestação de serviços, a Agência de Desenvolvimento Solidário (ADS) foi criada para atuar na política de emprego, auxiliando no fomento de alternativas de trabalho e renda para trabalhadores fora do mercado formal, sob a forma predominante de cooperativas. A justificativa política para tais ações escora-se no movimento de economia solidária da América Latina que, em geral, diz buscar ativar um tipo de envolvimento da sociedade civil marcado por outra racionalidade econômica, distinta da capitalista. No nível da elaboração teórica se soma a proposta da CUT um residual discurso socialista reconfigurado segundo a versão de Paul Singer, que advoga a necessidade de construção dos “implantes socialistas” para a realização da transição pacífica à nova sociedade transformada. A partir dessa compreensão, o socialismo seria alcançado sem a necessidade de se contrariar interesses de classe e sem eliminar o próprio capital, bastando que os empreendimentos econômicos cooperativos praticassem internamente a gestão democrática e estabelecessem relações econômicas tendo a justiça e a solidariedade por base...
Keywords: Central Unica dos Trabalhadores (Brasil); Sindicalismo; Economia solidária; Syndicalism